Comparison of 17β-estradiol, bisphenol-A and caffeine concentration levels before and after the water treatment plant - Graziela Taís Schmitt; Marcelo Oliveira Caetano; Vinícius Martins Marques; Amanda Gonçalves Kieling; Marie Launay; Lilia Itzel Acosta Muñiz; Luciana Paulo Gomes (IWA Publishing, 2023)
This article compares the concentration levels of 17β-estradiol (E2), bisphenol-A (BPA) and caffeine (CAF) in the Sinos River, Brazil, which is a source of drinking water and the presence of contaminants after the conventional treatment in a municipal water treatment plant (WTP). A total of nine sampling campaigns were carried out, with sample collection in the Sinos River, upstream and downstream of the WTP, in addition to a drinking water sample (DW). The samples were extracted with solid phase extraction (SPE) and the concentration by liquid chromatography coupled to mass spectrometry (LC-MS). The maximum concentration in the Sinos River was 6,127.99 ng·L−1 for E2, 3,294.63 ng·L−1 for BPA and 1,221.95 ng·L−1 for CAF. In drinking water, the concentration range of E2, BPA and CAF was from less than the Detection Limit (DL) up to 437.50 ng·L−1, <DL up to 2,573.34 ng·L−1 and <DL up to 832.30 ng·L−1, respectively. In conclusion, the concentrations of these pollutants present in the Sinos River are high, which may represent a negative environmental impact on this water source. Drinking water indicates the need for a new treatment process that could promote the removal of these compounds. HIGHLIGHTS The presence of three micropollutants was confirmed in the Sinos River, in southern Brazil.; 17β-estradiol (E2), Bisphenol-A (BPA) and Caffeine (CAF) have been detected in drinking water.; Correlations between the sampled locations were found.; Recommended for continuous monitoring of these substances.;